Alkalinization Scenarios in the Mediterranean Sea for Efficient Removal of Atmospheric CO2 and the Mitigation of Ocean Acidification - Butenschön, Momme; Lovato, Tomas; Masina, Simona; Caserini, Stefano; Grosso, Mario (Frontiers in Climate, 2021)
It is now widely recognized that in order to reach the target of limiting global warming to well below 2°C above pre-industrial levels (as the objective of the Paris agreement), cutting the carbon emissions even at an unprecedented pace will not be sufficient, but there is the need for development and implementation of active Carbon Dioxide Removal (CDR) strategies. Among the CDR strategies that currently exist, relatively few studies have assessed the mitigation capacity of ocean-based Negative Emission Technologies (NET) and the feasibility of their implementation on a larger scale to support efficient implementation strategies of CDR. This study investigates the case of ocean alkalinization, which has the additional potential of contrasting the ongoing acidification resulting from increased uptake of atmospheric CO2 by the seas. More specifically, we present an analysis of marine alkalinization applied to the Mediterranean Sea taking into consideration the regional characteristics of the basin. Rather than using idealized spatially homogenous scenarios of alkalinization as done in previous studies, which are practically hard to implement, we use a set of numerical simulations of alkalinization based on current shipping routes to quantitatively assess the alkalinization efficiency via a coupled physical-biogeochemical model (NEMO-BFM) for the Mediterranean Sea at 1/16° horizontal resolution (~6 km) under an RCP4.5 scenario over the next decades. Simulations suggest the potential of nearly doubling the carbon-dioxide uptake rate of the Mediterranean Sea after 30 years of alkalinization, and of neutralizing the mean surface acidification trend of the baseline scenario without alkalinization over the same time span. These levels are achieved via two different alkalinization strategies that are technically feasible using the current network of cargo and tanker ships: a first approach applying annual discharge of 200 Mt Ca(OH)2 constant over the alkalinization period and a second approach with gradually increasing discharge proportional to the surface pH trend of the baseline scenario, reaching similar amounts of annual discharge by the end of the alkalinization period. We demonstrate that the latter approach allows to stabilize the mean surface pH at present day values and substantially increase the potential to counteract acidification relative to the alkalinity added, while the carbon uptake efficiency (mole of CO2 absorbed by the ocean per mole of alkalinity added) is only marginally reduced. Nevertheless, significant local alterations of the surface pH persist, calling for an investigation of the physiological and ecological implications of the extent of these alterations to the carbonate system in the short to medium term in order to support a safe, sustainable application of this CDR implementation.